Factors Influencing Fishermen's Income at the Wotu Fish Auction Site in East Luwu Regency, Indonesia - Rusna; Agusdiwana Suarni; Abdul Khaliq; Andi Maghfirah Zainal; Sahabuddin N (IECON: International Economics and Business Conference, 2024)
This study aims to analyze the influence of working capital, catch volume, experience, and selling prices on the income of fishermen at the Wotu fish auction. The research employs a quantitative approach, utilizing data collected through questionnaires distributed to respondents directly related to the research topic. Data collection methods include observation and questionnaire distribution. The study incorporates both primary and secondary data sources. The research instrument applies the Likert scale to measure variables. Data analysis, conducted using SPSS version 25, reveals that working capital significantly affects income, catch volume also significantly impacts income, experience does not show a significant effect on income, and selling prices significantly influence fishermen's income at the Wotu fish auction.